Factors in Defending Australia’s Interests in the Pacific through Pacific ‘Step-up’ Foreign Policy Decision-Making in 2017-2018 - Sasikirana, Nasywa Amelia; Hidayat, Cecep (Jurnal Paradigma, 2025)
Australia makes the Pacific region a fundamental interest to defend its national interests. This commitment was made by launching a Pacific 'step-up' foreign policy in 2018 based on the 2017 Foreign Policy White Paper. Foreign policy decision-making is caused by external factors and internal factors. These external factors stem from the growing strategic competition between the United States and China in the Pacific as well as China's increasing influence that could shift Australia's influence as a traditional Pacific partner. Meanwhile, the internal factors stem from the perception of Australia's political elite towards the Chinese threat and public opinion that supports government intervention in the Pacific. The merger of external and internal factors prompted Australia to take action in 'balancing'. This is because the United States and China are partners in national interests, so the choice to establish relations with Pacific Island Countries (PIC) is the right choice. Meanwhile, the Australian government's efforts to counter the Chinese threat and the Australian Government's support for providing assistance to the Pacific helped drive the policy. The problem is studied by using the policy-making theory of Graham T. Allison and the concept of neoclassical realism to look at the process of Australian foreign policy-making related to changes in the rules-based order and domestic conditions of Australia. The method used in this study uses a qualitative approach. The results of this study show that Pacific ‘step-up’ foreign policy is capable of defending Australia's national interests